Implementasi Kebijakan Dalam Pengelolaan Desa Wisata di Kabupaten Bintan - Yusnita, Yeni; Samin, Rumzi; Subiyakto, Rudi (Metta : Jurnal Ilmu Multidisiplin, 2024)
Tourism has become an important source of local income in Bintan Regency. However, the implementation of tourism management policies in Bintan Regency still faces problems, both factual and theoretical, from various stakeholders. This research aims to analyze the implementation of policy using Edward III theory in managing tourism in Bintan Regency. The research method used is a qualitative descriptive approach by collecting secondary data in the form of government documents and primary data through direct interviews with informants, which were then analyzed deeply according to the findings on the ground. This study shows that the implementation of tourism management policies in Bintan Regency requires strong collaboration between the government, community, and relevant parties. Edward III emphasizes that structural variables, attitudes or dispositions of implementers, resources, and communication must be accompanied by the principle of building sustainable tourism villages, so that the problems that will be faced can be solved optimally. The barriers and challenges in implementing this policy must be overcome by every stakeholder. The government needs to focus more on developing local potential and increasing community capacity in managing tourism villages. In addition, the government also needs to provide training and mentoring to the community so that they can actively participate in managing tourism villages. Furthermore, the implementation of tourism management policies in Bintan Regency requires a strong commitment from the government, community, and relevant parties to increase community awareness and improve the quality of tourism village management. Therefore, it is hoped that successful tourism village management can be achieved in Bintan Regency that is ideal and sustainable.